Enhancing Employee Retention Through Talent Management Practices: A Semi-Systematic Literature Review: Meningkatkan Retensi Karyawan Melalui Praktik Manajemen Bakat: Tinjauan Literatur Semi-Sistematis - Shu, Efin (Institut Pariwisata dan Bisnis Internasional, 2024)
The high turnover rate in the hospitality industry has long been a significant challenge, with employees in this sector exhibiting high levels of mobility, even on a global scale. In 2023, the hospitality industry experienced the highest turnover rate compared to other sectors, making employee retention a critical managerial concern. This paper aims to address this issue by reviewing the factors that influence employees' intention to remain within the industry. Through an examination of existing literature, the study explores the contributions of talent management practices and employee-oriented Corporate Social Responsibility (CSR) initiatives to improving employee retention. The findings highlight the importance of work-life balance, quality of work-life, and employee-related CSR as key determinants in strengthening retention. The paper introduces the novel perspective that these factors should be viewed as interrelated components of a holistic approach to human resource management best practices. The urgency of addressing employee turnover in the hospitality sector is emphasized, given the industry's vulnerability to external, unpredictable challenges. This research contributes to the field by offering insights into effective human resource strategies that not only retain employees but also foster collaboration and enhance overall organizational performance. The paper provides practical recommendations for human resource managers to anticipate future workforce trends and align their strategies to promote sustainable employee engagement and retention in an increasingly dynamic and competitive industry.